Overactive bladder and its effects on sexual dysfunction among women. (16th September 2013) - Ergenoglu, Ahmet M.; Yeniel, Ahmet Özgür; Itil, Ismail Mete; Askar, Niyazi; Meseri, Reci; Petri, Eckhard
Abstract: Objective: To evaluate the relation between overactive bladder (OAB) and sexual dysfunction in sexually active nurses without stress urinary incontinence and pelvic organ prolapse. Design: Prospective, observational study. Setting: Tertiary care center: Population: 200 nurses, under 49 years of age. Method: Data were obtained with Turkish language‐validated questionnaires between January 2011 and June 2011. OAB was diagnosed using the Overactive Bladder Awareness Tool (OAB AT). Main outcome measures: Scores on the Overactive Bladder Symptom and Health‐related Quality of Life Questionnaire Short Form (OABq‐SF), the Health‐related Quality of Life Questionnaire Short Form (HRQOL), and the Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire Short Form (PISQ‐12). Results: Of the 127 enrolled volunteers, 51 were diagnosed with OAB. The mean age of the participants was 37.8 ± 7.3 years. After controlling for age, body mass index, and parity, OAB did not significantly affect PISQ‐12 scores, but significantly worsened OABq‐SF scores. No strong correlation was noted between the parts of the OABq‐SF and the domains of the PISQ‐12. Conclusion: OAB is a common problem among sexually active young women and significantly affects their quality of life. However, OAB‐related sexual dysfunction plays a limited role among sexually active nurses.